1996
DOI: 10.1002/(sici)1098-2345(1996)40:4<315::aid-ajp2>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Proximity relationships within a birth cohort of immature Japanese monkeys (Macaca fuscata) in a free-ranging group during the first four years of life

Abstract: This study was designed to characterize the proximity relationships among 20 immature Japanese monkeys (Macaca fuscata) of the same age in a free‐ranging group during the first 4 years of life. Most male and female immature monkeys showed a consistent preference for proximity within their cohort to certain same‐sex individuals whose dominance ranks were immediately adjacent to their own throughout the first 4 years. Such prolonged proximity relationships between peers of the same sex were largely a reflection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…Males displayed more play preferences than females, yearlings with high maternal rank had the largest social networks, and yearlings from larger matrilines displayed a greater number of proximity preferences. These patterns are consistent with results of previous studies of social behaviour of both wild and captive macaques (de Waal & Luttrell 1986; Ehardt & Bernstein 1987; Nakamichi 1996). Nonetheless, as in previous studies, sex, rank, and kinship failed to fully explain observed variation in the social relations of our animals.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Males displayed more play preferences than females, yearlings with high maternal rank had the largest social networks, and yearlings from larger matrilines displayed a greater number of proximity preferences. These patterns are consistent with results of previous studies of social behaviour of both wild and captive macaques (de Waal & Luttrell 1986; Ehardt & Bernstein 1987; Nakamichi 1996). Nonetheless, as in previous studies, sex, rank, and kinship failed to fully explain observed variation in the social relations of our animals.…”
Section: Discussionsupporting
confidence: 92%
“…Attraction to kin and to similarly-ranked conspecifics has been demonstrated numerous times by nonhuman primate researchers (de Waal & Luttrell 1986; Ehardt & Bernstein 1987; Nakamichi 1996). We note that for our subjects, attraction to similarly-ranked peers was not simply a result of attraction to kin.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This finding is consistent with previous research in juvenile macaques (Kojima, 1998; Nakamichi, 1996) and human children (Barbu, 2003; Feiring & Lewis, 1987), and demonstrates that segregation between the sexes becomes more marked as individuals mature. As discussed above, such segregation may serve important functions related to status-seeking for males, and investment in kin for females.…”
Section: Discussionsupporting
confidence: 92%
“…Time spent in proximity or social contact is a useful index for describing basic social relationships among group members (Takahata 1982;Nakamichi 1996), but it may not be adequate for analyzing which animal takes the active role in maintaining such a close distance. On the other hand, in social grooming, the performer and recipient are easily identified.…”
Section: Introductionmentioning
confidence: 99%